Structure influence on mechanical properties of Ti-W-B system nanocrystalline coatings - Sobol', O.V.; Dub, S.N.; Grigor`ev, O.N.; Podtelezhnikov, A.A.; Stetsenko, A.N. (Functional Materials, 2006)
The effect of structure on nano-hardness and elastic modulus of Ti-W-B nanocrystalline coatings prepared by triode sputtering has been studied. The material structure state has been found to change from cluster-crystalline (at low sputtering potentials U = 0.6 to 1.0 kV) to preferentially oriented-crystalline (at U > 2.2 kV). The texture perfection improvement with increasing U results in increased hardness and elastic modulus of the condensates. The maximum values were attained at U = 3.2 kV and amounted Н = 19.9 GPa and Е = 205 GPa for the cubic phase and Н = 37.9 GPa, Е = 389 GPa for the hexagonal phase, respectively.